Informação ambiental para o desenvolvimento sustentável nas escolas de Nova Soure/BA : uma proposta para o ensino fundamental II no contexto da energia eólica - Santos, Carina dos (2022)
Environmental information is the path to a more conscious society and is very important for decision-making and public policies. This research expatiate on the intervention for elementary education II in the city of Nova Soure in Bahia, from a benchmark of information aligned with environmental, economic and social development from the perspective of renewable energies, specifically wind energy from the Tucano Wind Complex. The theoretical framework has the premise of collaborating with the subject matter of wind energy in the pedagogical plan of schools, in terms of environmental education on renewable energies in the community and in teaching. The approach of this work is qualitative and descriptive, which had as a technical procedure a bibliographic research directed to sustainable development and the environment, as well as the premises of the National Curricular Common Base. For the preparation of the booklet, the references were taken into account, as well as the pedagogical plans of the science subjects of elementary education II. As a result, a digital booklet was developed based on the demands of the schools, so the production was structured in sections that address environmental information sources, sustainable development, renewable and non-renewable energies, wind energy and the Tucano Wind Complex, in order to reinforce the thematic discussions in pedagogical dynamics. It concludes that the booklet proposal is a source of information as a guiding reference for teachers who teach the discipline of Natural Sciences in school units, in thematic support to engage with students, as well as, in general, for access to the target audience in the city.